Health risk assessment of heavy metals in vegetables grown around battery production area (Scientia Agricola, 2014)
Battery production is one of the main sources of heavy metals that present great harm to human health even in low concentrations. Chromium (Cr), Cadmium (Cd) and Lead (Pb) were measured in edible portions of vegetables and soils around a battery production area in China, and the potential health risk of heavy metal contamination to the local population via vegetable consumption was evaluated. Their concentrations in edible portions of vegetables were 2.354 (0.078-14.878), 0.035 (0.003-0.230) and 0.039 (0.003-0.178) mg kg-1, respectively. Approximately 3 % of the Cd in the vegetable samples exceeded the maximum concentration allowable by national food safety criteria, although Pb content in all samples were within the criteria. Transfer factors (TF) from soils to vegetables were dependent on vegetable species. Leguminous vegetables were more likely to accumulate Cr, while leaf vegetables tended to show higher levels of concentration of Cd and Pb. Melon vegetables demonstrated a relatively low capacity for accumulating the heavy metals studied. TF were positively correlated with soil organic matter and negatively correlated with soil pH. The mean estimated daily intake of Cr, Cd and Pb via dietary consumption of vegetables was 0.011, 1.65 × 10-4 and 1.84 × 10-4 mg kg-1 of body weight per day, respectively, levels that were much lower than the reference doses recommended by USEPA (U.S. Environmental Protection Agency) and JECFA (Joint FAO/WHO Expert Committee on Food Additives), indicating that the potential health risk of Cr, Cd and Pb exposure via vegetable consumption to the local population around this battery production area could be negligible.